Preliminary Studies into the Characterization of Chemical Markers of Decomposition for Geoforensics - Swann, Lisa; Chidlow, Geoffrey; Forbes, Shari; Lewis, Simon (Blackwell Publishing, 2010)
In this paper, we report the results of our preliminary studies into chemical characterization of the fluids produced during decomposition in the absence of a soil matrix. Pig (Sus domestica) carcasses were used to model the human decomposition process in two separate locations, Western Australia (Perth) and Canada (Oshawa). Analysis involved simple dilution and filtration of the decomposition fluids followed by gas chromatography?mass spectrometry. Several previously unreported compounds were detected in the decomposition fluid samples during the trials, including benzeneacetic acid, benzenepropionic acid, 2-piperidone, and isocaproic acid. Possible biosynthetic pathways for some of the compounds produced are proposed. Further research trials are required, particularly in the presence of soil matrices.